Identification of GH10 xylanases in strains 2 and Mz5 of Pseudobutyrivibrio xylanivorans - Grilli, Diego Javier (2014)
Genes encoding glycosyl hydrolase family 11 (GH11) xylanases and xylanases have been identified from Pseudobutyrivibrio xylanivorans. In contrast, little is known about the diversity and distribution of the GH10 xylanase in strains of P. xylanivorans. Xylanase and associated activities of P. xylanivorans have been characterized in detail in the type strain, Mz5. The aim of the present study was to identify GH10 xylanase genes in strains 2 and Mz5 of P. xylanivorans. In addition, we evaluated degradation and utilization of xylan by P. xylanivorans 2 isolated from rumen of Creole goats. After a 12-h culture, P. xylanivorans 2 was able to utilize up to 53 % of the total pentose content present in birchwood xylan (BWX) and to utilize up to 62 % of a ethanol-acetic acid-soluble fraction prepared from BWX. This is the first report describing the presence of GH10 xylanase-encoding genes in P. xylanivorans. Strain 2 and Mz5 contained xylanases which were related to GH10 xylanase of Butyrivibrio sp. Identifying xylanase-encoding genes and activity of these enzymes are a step toward understanding possible functional role of P. xylanivorans in the rumen ecosystem and contribute to providing an improved choice of enzymes for improving fiber digestion in ruminant animals, agricultural biomass utilization for biofuel production, and other industries.